Pengaruh Lingkungan Madrasah Terhadap Motivasi Belajar Siswa MTs Sunan Kalijogo Rejosari Kalidawir Kabupaten Tulungagung - Annisa Rif’atul Husniah; Jani Jani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Basically, each student's learning motivation is different. A safe, comfortable and peaceful madrasah environment will increase student motivation in learning, so that learning goals can be achieved well. In this case, researchers are interested in researching the influence of the Madrasah environment on students' learning motivation at MTs Sunan Kalijogo Rejosari Kalidawir, Tulungagung Regency. The formulation of the problem taken in this research is whether there is an influence of the madrasa environment on the learning motivation of MTs Sunan Kalijogo Rejosari Kalidawir Tulungagung Regency students? Meanwhile, the aim of this research is to determine the influence of the madrasa environment on the learning motivation of students at MTs Sunan Kalijogo Rejosari Kalidawir, Tulungagung Regency. This research uses a survey research method with a quantitative research type. Data collection techniques use observation, questionnaires and documentation. The population was 176 and the sample was 36 students taken from 20% of the total population using the Probability Sampling technique. The research results obtained were based on hypothesis testing using Pearson product moment correlation analysis. The values ​​obtained are the Pearson correlation value is 0.833 > 0.3291 and the significance value is 0.000 < 0.05. This means that hypothesis testing shows that Ha is accepted and H0 is rejected. So it can be concluded that the madrasa environment influences the learning motivation of students at MTs Sunan Kalijogo Rejosari Kalidawir, Tulungagung Regency.